Molecular phylogeny of two unusual brown algae, Phaeostrophion irregulare and Platysiphon glacialis, proposal of the Stschapoviales ord. nov. and Platysiphonaceae fam. nov., and a re-examination of divergence times for brown algal orders - Kawai, Hiroshi (Journal of phycology, 2015)
© 2015 The Authors. Journal of Phycology published by Wiley Periodicals, Inc. on behalf of Phycological Society of America.